Precise Mapping of Otp Expressing Cells Across Different Pallial Regions Throughout Ontogenesis Using Otp-Specific Reporter Transgenic Mice - Morales, Lorena; González-Alonso, Alba; Desfilis, Ester; Medina, Loreta (Frontiers in Neural Circuits, 2022)
Taking advantage of two Otp-specific reporter lines of transgenic mice (Otp-eGFP and Otp-Cre; Rpl22-HA), we identify and describe different Otp cell populations across various pallial regions, including the pallial amygdala, the piriform cortex, the mesocortex, the neocortex, and the hippocampal complex. Some of these populations can be followed throughout development, suggesting migration from external sources (for example, those of the pallial amygdala and at least some of the cingulate cortex). Other cells become visible during postnatal development (some of those in the neocortex and hippocampal formation) or in adulthood (those of the parahippocampal lobe), and seem to be produced locally. We discuss the possible role of Otp in these different populations during different moments of ontogenesis. We also analyze the connectivity patterns of some of these cells and discuss their functional implications. For example, our data suggest that Otp cells of the pallial amygdala might be engaged in networks with other Otp cells of the medial amygdala with the same embryonic origin, and may regulate specific aspects of social behavior. Regarding Otp cells in the parahippocampal lobe, they seem to be projection neurons and may regulate hippocampal function during spatial navigation and memory formation. The two reporter transgenic mice employed here provide very powerful tools for high precision studies on these different Otp cells of the pallium, but careful attention should be paid to the age and to differences between lines.